Econometrics of Climate Change: The Impact of Emission Reduction Policies on Economic Growth in Southeast Asia - Sugihartini, Pegi (Sekolah Tinggi Agama Islam Kuningan, 2025)
Climate change has become a serious threat to economic stability, especially in the Southeast Asian region, which is vulnerable to negative impacts due to industrial activities and resource exploitation. Carbon emission reduction policies, implemented through various regulations and incentives, are expected to help reduce these impacts. However, there are concerns that this policy could hamper economic growth in the region. This study aims to explore the impact of emission reduction policies on economic growth in Southeast Asia through qualitative methods. Using a case study approach and thematic analysis, this study examines insights from policymakers, environmental experts, and industry representatives in a number of Southeast Asian countries. Data were obtained through in-depth interviews and analysis of relevant environmental policy documents. The results of the study show that there is a significant variation in the acceptance and impact of emission reduction policies on economic growth in various countries, which is influenced by the economic dependence on the high-emission industrial sector and the readiness of each country's green infrastructure. These findings provide guidance for policymakers to develop balanced emission reduction policies, prioritizing environmental sustainability while supporting economic growth